1989
DOI: 10.1002/anr.1780320808
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the center for epidemiological studies depression scale in arthritis populations

Abstract: Using data from 3 studies of patients with rheumatoid arthritis, we examined the extent to which responses to items in the Center for Epidemiological Studies Depression Scale (CES-D) are influenced by aspects of the disease process other than depression. Our findings suggested that 4 CES-D items (i.e., "I felt that everything I did was an effort," "I felt hopeful about the future," "My sleep was restless," and "I could not get going") may be influenced by aspects of the disease process and, thus, are not neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
155
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(162 citation statements)
references
References 17 publications
(9 reference statements)
5
155
1
1
Order By: Relevance
“…The CES-D is a 20-item validated scale with a score range from 0 to 60 with a score of 16 or higher generally accepted as the cut score indicating probable clinical depression [3,9,11,19]. The CES-D is often used to study community-based, elderly persons and has recently been endorsed by Smarr and Keefer [24] for use in patients with arthritis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CES-D is a 20-item validated scale with a score range from 0 to 60 with a score of 16 or higher generally accepted as the cut score indicating probable clinical depression [3,9,11,19]. The CES-D is often used to study community-based, elderly persons and has recently been endorsed by Smarr and Keefer [24] for use in patients with arthritis.…”
Section: Methodsmentioning
confidence: 99%
“…Despite high surgical success rates, as many as 25% of patients report compromised postoperative functioning and persistent pain although having a stable implant [2]. Recent research has indicated that psychologically based impairments and disorders such as pain catastrophizing, anxiety, and depression increase the risk of poor patient outcomes after TKA [3]. Measures of depressive symptoms tap the underlying construct of depression, but they also capture related symptoms such as anxiety and general emotional distress, which may manifest as difficulty sleeping, poor concentration, and negative feelings in patients.…”
Section: Introductionmentioning
confidence: 99%
“…On these questionnaires, patients reported changes in demographic data, health, medications, pain levels (100-mm VAS), global assessment of disease activity (100-mm VAS), the Disability Index (DI) of the Health Assessment Questionnaire (HAQ) (46), and the Center for Epidemiologic Studies Depression scale (CES-D) (47).…”
Section: Methodsmentioning
confidence: 99%
“…Given the unique features of RA, items included on this shortened scale may not discriminate well between individuals with and without MDD who also have RA. Prior research indicates that 2 of the CES-D items included on the shortened version of the scale ("I felt that everything I did was an effort" and "My sleep was restless") may be influenced by aspects of RA and thus not necessarily due to depression (3,16). These items were included in the present study because the purpose of the project was to assess the efficiency of the overall shortened scale developed by Santor and Coyne.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the commonly used CES-D cutoff scores often result in a high percentage of false positives, with numerous individuals being categorized as depressed who, in fact, do not meet the criteria for MDD. A high number of false positives may be especially problematic in populations experiencing RA because symptoms that are attributable to the condition may overlap the symptoms of MDD (3,16).…”
Section: Introductionmentioning
confidence: 99%